Financing Human Development in Africa, Asia and the Middle East - Sánchez, Marco V. (The United Nations Series on Development, 2014)
This book is available as open access through the Bloomsbury Open Access programme and is available on bloomsburycollections.com. How much would poor nations need to invest to eliminate poverty, get all children in school and provide adequate basic health care for all? Can they afford it? Financing Human Development in Africa, Asia and the Middle East provides some clear answers to these questions. The contributors assess feasible financing strategies underpinning actions to enhance human development in pursuance of the United Nations' Millennium Development Goals (MDGs). The contributors analyse these strategies in the context of broader concerns of economic development in nine countries in Africa, Asia and the Middle East. The assessments stress the importance of redesigning macroeconomic policies so as to make these more supportive of long-term economic growth and employment creation, while ensuring sufficient investments in human development in order to end poverty and overcome deep-rooted inequalities.